Perancangan Buku Panduan Penerapan Logo Dan Identitas Visual Institut Sains Dan Teknologi Al-Kamal - Affan Fajar Aprilio; Abidin M; Ateng Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2026)
A logo is the identity of a company that is easiest to recognize. The logo itself is part of a company's image. A good logo display and appropriate placement, reflects a good impression on the company or agency. Al-Kamal Institute of Science and Technology as an educational institution that has been established since 40 years ago and graduated thousands of students into scholars. Trust must be maintained in communicating with government agencies that oversee the implementation in higher education, the academic community of fellow institutions to build a good image in the community, especially for marketing purposes. Institutions need to have an identity for a good image in the form of visual branding, Consistent use of visual identity will support the image of the institution. Currently, there are still many applications of the Al-Kamal Institute of Science and Technology logo that are still not good in terms of position, proportion and composition. The design of the Guidebook for Logo Application and Visual Identity of the Al-Kamal Institute of Science and Technology is one of the efforts so that the application of the logo can be carried out with appropriate guidance. So as to increase trust and a good image. As a result of this research process, the author will design a guidebook for the application of logos and visual identities for the Al-Kamal Institute of Science and Technology as a reference for the institution's visual identity, as well as supporting media such as x-banners, brochures, car branding, and merchandise.